Advances in second hematopoietic stem cell transplantation - Yan, Sijia; Zhu, Xiaojian; Xiao, Yi (Frontiers in Immunology, 2024)
Hematopoietic stem cell transplantation (HSCT) is a widely used treatment for malignant hematological diseases; however, some patients inevitably experience relapse. Therefore, for patients who relapse after the first HSCT (HSCT1), a standard treatment regimen must be developed. A second hematopoietic stem cell transplantation (HSCT2) is a possible treatment option. Several studies have analyzed the feasibility of HSCT2. Previous studies have shown that various factors may affect the efficacy of HSCT2, including the hematopoietic cell transplantation comorbidity index, duration of remission after HSCT1, occurrence of chronic graft-versus-host disease, and disease status before HSCT2. However, the selection of donors for HSCT2 does not affect the transplantation efficacy. HSCT2 also presents a risk of relapse, and the prognosis of patients after relapse is poor. Further research on the treatment of patients after relapse is warranted.